2014
DOI: 10.3184/003685014x13994743930498
|View full text |Cite
|
Sign up to set email alerts
|

Cronobacter: An Emergent Pathogen Causing Meningitis to Neonates through their Feeds

Abstract: QiongQiong Yan is a graduate student matriculating at University College Dublin Centre for Food Safety. Her PhD research has focused on understanding the survival mechanisms of Cronobacter under low moisture growth conditions using molecular methods such as RNA sequencing and transposon-directed insertion site sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…These bacteria have been associated with cases of illnesses in neonates for which fatality rates ranging between 40 and 80% have been reported (Tall et al, 2014). Clinical manifestations of infection include necrotizing enterocolitis, septicemia and neonatal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria have been associated with cases of illnesses in neonates for which fatality rates ranging between 40 and 80% have been reported (Tall et al, 2014). Clinical manifestations of infection include necrotizing enterocolitis, septicemia and neonatal meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance studies have shown that Cronobacter contaminates a multitude of foods and environments, including water, infant foods (such as powdered infant formula (PIF) and follow-up formulas), dried milk protein products, cheese, licorice, candies, dried spices, teas, nuts, herbs, filth and stable flies, and PIF or milk powder production facilities and household environments [33]. The microarray was developed during 2009-2013 through the leveraging of WGS efforts of a five-member International Cronobacter consortium.…”
Section: Multiple Species Component Arraymentioning
confidence: 99%
“…4 While infantile Cronobacter infections are often linked to the consumption of reconstituted, temperature-abused, intrinsically or extrinsically contaminated powdered formulas, these organisms are also found associated with other foods and food production environments, such as that of manufacturing facilities of dried foods, thereby posing a risk to susceptible consumers. 5 Previous studies by Lehner et al and da Silva Araujo et al reported the presence of 2 and 3 QS molecules in different Cronobacter spp., respectively. 6,7 Singh et al 3 identified a group of long chain AHLs, of C6-C18 in length, using High Performance Liquid Chromatography and Liquid Chromatography-High Resolution Mass Spectrometry in combination with 2 different QS screening bioassays based on Chromobacterium violaceum CV026 and Agrobacterium tumefaciens NTL4(pZLR4).…”
mentioning
confidence: 92%